Vallas polifuncionales como medio publicitario para la provincia de Chimborazo - Fiallos Eras, Dayana Nicole (2025)
Currently our country lacks creative and eye-catching advertising media, among these I want to highlight the billboards, which although they are based on various styles and types of billboards, they lack creativity, so my research is established from the observer as the shortage of billboards within the province of Chimborazo, being a place that is constantly visited, the potential sites are unknown, based on its history and representative icons of each canton, the proposal of multifunctional billboards is shown as a tourist medium, durable, innovative and highlighting the province with a representative element based on the color of its flag, with the help of Robert Scott's methodology and an investigation based on a mixed approach in order to obtain a broad analysis of the problems that the province of Chimborazo currently has, with the help of instruments such as observation sheets to analyze the current fences on the roads, which will help verify that these fences are not used in the best way and are simply shown in the traditional way as visual and environmental pollution, taking into account three main routes divided into two phases, surveys of national and foreign tourists, interviews with government authorities and experts in the area, we will obtain a new, striking proposal, functional 24 hours a day and with several uses in addition to promoting the sites, cantons and the province, taking a souvenir that makes more people interested in this new initiative.